Suicidal ideation and self‐harm among youths in Norway: associations with verbal, physical and sexual abuse. Issue 2 (22nd January 2014) - Mossige, Svein; Huang, Lihong; Straiton, Malanie; Roen, Katrina
Abstract: Using data from a national survey ( n  = 6979) of young people in their last year in Norwegian secondary schools in 2007 (aged 18–19), this paper explores the relationship between sexual abuse and experiences of violence among young people in Norway and their reporting of suicidal ideation and self‐harm. This investigation includes three types of abuse experienced by young people: non‐physical, physical and sexual. We investigate suicidal ideation and two types of self‐harming behaviour: non‐suicidal self‐injury and suicidal self‐injury. The analyses that are reported involve descriptive analysis, chi‐square and t ‐tests, and logistic regression. The hypothesis that was confirmed by the analysis was that being subject to sexual abuse or other violence was associated with increased risk of self‐harm. The hypothesis that was partially supported by the analysis was that violence experienced during childhood would have more effect on suicidal ideation and self‐harm than violence experienced at a later age. Contrary to our expectations, it was found that peer bullying has a stronger effect on young people's suicidal ideation and self‐harming behaviours than sexual abuse or physical violence. The implications of these findings for practitioners working with children and youth involve raising awareness about the long‐term effects of verbal, physical, sexual and witnessed abuse.